ANALISIS KUALITAS PENGELOLAAN GEDUNG TERHADAP KEPUASAN PELANGGAN MENGGUNAKAN METODE SERVQUAL DAN MODEL KANO (STUDI KASUS : PT.TLP DI GEDUNG TCC) - Razul harfi; Dwina Suciati Nurrohmah (Fakultas teknik Universitas Muhammadiyah Jakarta, 2017)
PT. TLP is a company which employs the service area and the task is to preserve the TCC building and to fulfill the needs of its users through providing complete facilities and service. But have the customers satisfied with the facilities and services? Therefore, the aim of this research is to measure the level of customer satisfaction, to determine which service attributes are prioritized for improvements, and the efforts to the improvement. The method used is servqual methods and models of canoes. The servqual method is intended to determine the level of customer satisfaction, while the canoe models is for finding out the preferred improvement services. The result of servqual analysis shows that there is a gap of all attributes and the scores are negative. These means that the quality of customer service of PT.TLP is not satisfactory. The average percentage for the customer's perception is 75.25% and 88.10% for expectations. Moreover, the canoe analysis also shows that out of 32 service attributes, there are 25 attributes that should be corrected, namely 3 services are categorized Attractive, 5 service category One-dimensional, and 17 services are categorized ‘Must be’. Having integrated the servqual with canoes model, it is obtained that there is a sorting of the improvements priority, then determined improvements suggestion to evaluation for the company, such as setting the lobby and courtyard regularly, implementing the service with heart, socializing the call center, having the training regularly, making the data collection and the disposition of the vehicle, also testing of fire protection and alarm regularly